Chafarizes de Paris - Gustave Fulgence (Confins)
Paris offers to passers-by a little more than 1,100 freely accessible drinking water points, all of them to be found on an interactive map available on the Eau de Paris website (http://www.eaudeparis.fr/ ), where there is also a presentation of its system of collection, treatment and distribution of water, whose public fountains are only the most visible face